TEACHER’S IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING (CLT) IN TEACHING SPOKEN LANGUAGE AT SECONDARY SCHOOL - Shofiah Nur Azizah; Yusup Supriyono; Agis Andriani (Journal of Applied Linguistics (ALTICS), 2021)
Nowadays, English is regarded as a crucial language to master, particularly for communicative competence. One of many approaches to help learners to master English is Communicative Language Teaching (CLT). CLT has been recognized as the most common approach to promoting communicative competence. Moreover, it has been implemented by many English as a Foreign Language (EFL) countries involved in Indonesia. This study aims to determine the CLT implementation as performed by an EFL teacher in teaching spoken language at Secondary School. To achieve the aim, this study used a descriptive case study as a research design. The participant of the study was an EFL teacher who implements CLT in teaching spoken language. The data were collected through semi-structured interviews, classroom observation, and document analysis. The result of the data collection was analyzed by using Qualitative Data Analysis from Miles, Huberman, and Saldaña (2014). The findings revealed that the CLT implementation has been performed by an EFL teacher through three components. Those are seen from the teacher’s way of deciding the material, being a facilitator in the teaching-learning process, and applying teaching-learning strategies. This research indicates that the use of the CLT approach could facilitate learners to develop communicative competence skills. Keywords: Communicative Language Teaching (CLT), Spoken Language.